The Effect Of Semi-Fowler Position On Oxygen Saturation In Patients With Chronic Heart Failure In West Kalimantan - Novikadarti Rahmah, Gabby; Ibnu Kahtan, Muhammad; Fauzan, Suhaimi; Lili Neri, Ervina (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2024)
Introduction: Heart disease is the number one cause of death in the world every year. CHF patients can show various clinical symptoms in the respiratory and cardiovascular systems. Monitoring oxygen saturation values and respiration rate is an important thing to do. Appropriate management for patients with CHF can improve and stabilize the patient’s respiratory status. Aims: This research aims to analyze the effect of the semi-fowler position on oxygen saturation. Methods: This research was quasi-experimental research with Non Equivalent Control Group Pre-Post. The population in this study were patients with CHF who were undergoing treatment at RSUD dr. Soedarso Pontianak. A purposive sampling method was employed in this study. Variables were semi-fowler position and oxygen saturation. Data collection used a field data observation checklist. The result of this study was analyzed using a paired T-test. Result: Statistical tests showed a difference in oxygen saturation before and after semifowler positioning in patients with CHF. The P value proved it was 0,0004. Conclusion: The effect of the semi-Fowler position can provide breathing comfort and improve sleep quality for patients with CHF.